2003
DOI: 10.1021/ja035427v
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Residual Dipolar Couplings from Denatured Proteins

Abstract: Effects of steric obstruction on random flight chains are examined. Spatial probability distributions are elaborated to calculate residual dipolar couplings and residual chemical shift anisotropy, parameters that are acquired by NMR spectroscopy from solutes dissolved in dilute liquid crystals. Calculations yield chain length and residue position-dependent values in good agreement with simulations to provide understanding of recently acquired data from denatured proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
121
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 28 publications
6
121
0
1
Order By: Relevance
“…By using residual dipolar couplings (RDCs) from NMR, Shortle and Ackerman (27) showed that native-like topology persists under strongly denaturing conditions in a truncated staphylococcal nuclease. Contention about the origin of RDCs in unfolded proteins notwithstanding (28), other NMR methods also detect structure in the unfolded state. By using triple-resonance NMR, native-like topology has been observed in protein L (29).…”
Section: Discussionmentioning
confidence: 99%
“…By using residual dipolar couplings (RDCs) from NMR, Shortle and Ackerman (27) showed that native-like topology persists under strongly denaturing conditions in a truncated staphylococcal nuclease. Contention about the origin of RDCs in unfolded proteins notwithstanding (28), other NMR methods also detect structure in the unfolded state. By using triple-resonance NMR, native-like topology has been observed in protein L (29).…”
Section: Discussionmentioning
confidence: 99%
“…We investigate whether a correlation exists between the magnitude of the RDCs and the AR of the individual members in the ensemble of unfolded state proteins. High ARs are expected for individual chains in any random-walk model even though the ensemble average is spherical (33,44). The AR is defined as (I z )͞ ͌ I x I y , where I x , I y , and I z are the moments of inertia for the given conformation in ascending order.…”
Section: Radius Of Gyrationmentioning
confidence: 99%
“…Shortle and coworkers (1,(26)(27)(28) argue that denatured proteins retain some native-like topology in the denatured state. However, others propose simpler explanations related to the fundamental nature of random coils in aligned media (33) or to short stretches of extended conformations (29,34).…”
mentioning
confidence: 99%
“…42 For statistical random coils, RDCs are predicted to have a characteristic profile, uniform throughout the polypeptide except at the termini, where they approach zero due to increasingly isotropic flexibility. 48 Deviations from such a profile may be an indication of secondary structure preferences with a decrease of RDC amplitude correlated with local compactness or flexibility. 49 For aS, it has also been suggested that large amplitude RDCs in the C-terminal tail of the protein may report on long-range transient contacts between the C-terminus and regions in the N-terminal lipid-binding domain.…”
Section: Residual Dipolar Couplingsmentioning
confidence: 99%